Prevalence and risk factors of metabolic associated fatty liver disease in lean patients with bipolar disorder: a retrospective cross-sectional study - Lei, Weihong; Li, Jiahuan; Liu, Yiyi; Wang, Ying; Wu, Qing (Frontiers in Endocrinology, 2025)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) in lean individuals indicates metabolic dysfunction and elevates risks of metabolic and cardiovascular diseases. Thus far, no studies have specifically examined the prevalence and risk factors of MAFLD in lean individuals with bipolar disorder.MethodsThis retrospective study included 1,072 patients aged 18 to 60 years. Participants were classified into two groups based on their Body Mass Index (BMI): those with a BMI ≥24 kg/m² were categorized as overweight or obese, while those with a BMI <24 kg/m² were defined as lean. Data were extracted from inpatient records at the Anhui Mental Health Center.ResultsMAFLD prevalence markedly differed between groups (lean: 10.5% vs. overweight/obese: 76.3%, p<0.001). Among lean BD patients, MAFLD-positive and MAFLD-negative subgroups significantly differed in: age, onset age, illness duration, BMI, ALT, key metabolic indices, marital status, diabetes, and hypertension. Stepwise binary logistic regression analysis revealed that fasting blood glucose level, triglyceride level, gamma-glutamyl transferase (GGT) level, female gender and diabetes status were significant risk factors for MAFLD, while high-density lipoprotein (HDL) level was identified as a protective factor.ConclusionMAFLD is clinically relevant in lean BD patients. Fasting blood glucose level, triglyceride level, GGT level, female gender, and diabetes status were significant risk factors for MAFLD, whereas HDL level was a significant protective factor. Given the potential harm of MAFLD, it is essential to enhance vigilance and underscore the necessity of monitoring MAFLD among individuals with bipolar disorder, especially those who are lean.